2012
DOI: 10.1016/j.actbio.2012.07.033
|View full text |Cite
|
Sign up to set email alerts
|

A naturally derived cardiac extracellular matrix enhances cardiac progenitor cell behavior in vitro

Abstract: Myocardial infarction (MI) produces a collagen scar, altering the local microenvironment and impeding cardiac function. Cell therapy is a promising therapeutic option to replace the billions of myocytes lost following MI. Despite early successes, chronic function remains impaired and is likely a result of poor cellular retention, proliferation, and differentiation/maturation. While some efforts to deliver cells with scaffolds attempt to address these shortcomings, they lack the natural cues required for optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(138 citation statements)
references
References 61 publications
3
131
1
Order By: Relevance
“…However, quantitative evaluation of CPC behaviour in contact with scaffolds showed that they did not proliferate after 1-14 days of culture time. In the future, cell behaviour could be further improved by scaffold surface functionalization with bioactive peptides/ proteins of the natural cardiac extracellular matrix (ECM) [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, quantitative evaluation of CPC behaviour in contact with scaffolds showed that they did not proliferate after 1-14 days of culture time. In the future, cell behaviour could be further improved by scaffold surface functionalization with bioactive peptides/ proteins of the natural cardiac extracellular matrix (ECM) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has described the potential benefits of ECM scaffold materials derived from homologous tissue versus heterologous tissue when used in selected anatomic locations. 2,[4][5][6][7][8][9][10][11] The homologous ECM can preferentially maintain tissuespecific cell phenotypes, [4][5][6][7] promote cell proliferation, 6,8 induce tissue-specific differentiation, 9 and enhance the chemotaxis of stem cells. 2,10,12 However, the preference or necessity for tissue-specific ECM has not been shown for all therapeutic applications.…”
mentioning
confidence: 99%
“…Both of these factors have been shown to promote the tissue-specific cell phenotype and function. [24][25][26][27][28] Clearly, in the experiments presented here, the ECM is not sufficient under the culture conditions used (DMEM + 10% FBS, perfusion, no ventilation) to maintain neonatal, rat lung epithelial phenotypes. Instead, these cells appear to undergo an EMT.…”
Section: Discussionmentioning
confidence: 99%